A productions and operations management study on Vinyl Resources, Inc. - Bo-ot, Jose Juan Miguel R. (College of Engineering, 2001)
This paper studied the Production and Operations Management aspect of Vinyl Resources Inc., a manufacturer of refrigerator gaskets. The company is one of only two local manufacturers of fused gaskets. Over the years, it has undergone backward vertical integration and increase in its plant utilization capacity. These were made in an attempt to strengthen the company's hold in their respective industry. However, production problems were still noted in initial plant visits. The different aspects of the company were documented and analyzed. In the process, major productions and operations problems were identified. Problems in forecasting, workforce planning, and inventory systems were noted as the most significant problems crippling the company. Possible alternatives through the use of Production and Operations Management tools were recommended. The use of forecasting with seasonality index was determined to be the best solution for the company sales forecasting. The addition if two workers (one in punching and the other in mitering) was found to decrease overtime cost in the company. Finally, lowering of the current safety stock level by 75% would lessen the capital investment on imported raw materials. Other problems noted were the low machine utilization and disruption of walk-in customers to the regular production schedule. These were left as areas for further study.